2017
DOI: 10.1007/s00266-017-0973-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of In Situ Septoplasty and Extracorporeal Subtotal Septal Reconstruction in Crooked Noses: A Randomized Self-Controlled Study

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Consistent with the current study results, Gode et al, reported that there was no statistically significant difference in the nasal scores between extracorporeal septoplasty and Insitu groups [27].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the current study results, Gode et al, reported that there was no statistically significant difference in the nasal scores between extracorporeal septoplasty and Insitu groups [27].…”
Section: Discussionsupporting
confidence: 91%
“…Fifty-nine articles were selected for a full review with 17 meeting the inclusion criteria. 6-10,12-22 Of the 17 studies selected, 10 studies recorded subjective functional outcome data, four studies provided objective functional outcome data, three studies provided subjective aesthetic outcome data, and six studies provided objective aesthetic outcome data—Table 1. Three studies reported the complication rate with no functional and/or aesthetic outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Jang et al utilized a 4 tier scale for grading appearance (excellent, good, moderate, or poor) provided by the patient postoperatively, while Gode et al utilized a VAS; nonetheless, both studies showed statistically significant improvement in patients’ aesthetic perception. 7,13 In contrast, Serna et al utilized third-party otolaryngologists to compare preoperative and postoperative photos using a Likert scale (completely straight, almost straight, deviated, very deviated, or severely deviated) and scored all but 5% as improved by at least one step (eg, from deviated to almost straight). 21 Due to the heterogeneity of scoring methods, a meta-analysis was not performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete cartilaginous and bony septum was then excised along its superior border except for the remaining few millimeters of the dorsal strip at the keystone area and removed in 1 piece if possible. 5 Several technical options were used to create a straight septal plate which needs usually the dimensions of 30 mm. in horizontal and 18-20 mm.…”
Section: Operative Procedures Group A: It Included 30 Patients Subjecmentioning
confidence: 99%